Outcomes Following Pars Plana Vitrectomy for Severe Ocular Trauma - Natalia K. Bober; Neruban Kumaran; Tom H. Williamson (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To investigate outcomes and presenting characteristics for subjects undergoing pars plana vitrectomy for ocular trauma. Methods: Retrospective study of 113 patients who underwent pars plana vitrectomy for severe ocular trauma at [name deleted to maintain the integrity of the review process] between 1999 and 2018. Data were collected on age, gender, initial and final visual acuity (LogMAR), mode of injury, type of injury, number of surgeries performed, follow-up duration, type of tamponade, presence of phthisis, and retinal detachment. The Birmingham Eye Trauma Terminology System (BETTS) was employed. Results: We identified assault and contusion injuries to be the most common mode and type of ocular injury in our cohort. Furthermore, through follow-up we noted a varied number of operations required by patients presenting with ocular trauma and a statistically significant improvement in visual acuity from 1.73 ( ± 0.86) LogMAR to 1.17 ( ± 1.03; p < 0.01) LogMAR. A statistically significant difference in final visual acuity was also noted between BETTS classified type of injury groups (p < 0.01). Notably, only 7.3% and 8.2% of patients developed phthisis or a persisting retinal detachment, respectively, during follow-up. Conclusion: Our study demonstrates that ocular trauma requiring pars plana vitrectomy can require a varied number of operations with a guarded visual prognosis. However, a small percentage will proceed to develop phthisis following intervention.